Semantic Analysis of the Lyrics of "Gēchàng Zǔguó (歌唱祖国)" by Wang Xin - Pravitasari, Khoirunnisa Herlistia; Agwinanda, Almira; Pamuji, Dian Yuni (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
National song lyrics have great potential as a linguistic medium in conveying ideology and shaping the collective spirit of society. Amid increasing attention to the role of language in the construction of National identity, it is important to examine how meaning in song lyrics works Semantically. This study analyses the Semantic meaning in the lyrics of the song "Gēchàng Zǔguó (歌唱祖国)" by Wang Xin using Leech's (1974) theoretical approach. This song was chosen because it contains the value of Nationalism and Chinese ideological symbols. The method used is Descriptive Qualitative with observation, recording and documentation techniques. The results show that Conceptual meaning dominates the song lyrics, especially through Geographical representation, State symbols, and the role of the people. In addition, the Connotative and Affective meanings also reinforce the spirit of nationality, love for the country, and historical pride. The song proves that lyrics can be a linguistic medium that conveys National ideology and identity.